Beyond the Skin Tone: Colourism and Systemic Racism in Toni Morrison’s God Help the Child (2015) - Hadj Kouider, Younes; Kourdourli, Abdelkade (Faculty of Letters and Foreign Languages Department of English, 2023)
The current study seeks to assess and investigate skin tone and racial prejudice as an issue within the systemic racism in American culture. This study adopts a historical, analytical, and qualitative approach.The key results of the current study demonstrate that colourism and internalized racism are not the result of the racial and cultural inferiority of black people in the United States, nor are they the result of white domination. However, they are the result of a timeless systemic racism that has gone unnoticed throughout American history.The research contributes to dispel stereotypes of black victims and white domination in America